Juridical Review Process Completion Code Violation of Notary - Eli Tri Kursiswanti; Yeremias Tony Putrawan; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study were 1) To explain the juridical review process completion code violation of notary, 2) To explain the process of resolving the obstacles and solutions notary code violations.The methods in this research is juridical-empirical approach. Judicial approach used to analyze a wide range of laws and regulations related to the implementation of sanctions for violations of the code of conduct notary, In this study, then this kind of research will be a descriptive analysis that describes, depicts or expressessanctions for violations of the code of notary conduct.Based on the results of this study concluded that 1) Notary is a public official who has the authority to make an authentic deed as an evidence that has the strongest evidence in civil law. Notary profession in practice arranged in a special instrument that Notary Code. Not with standing remains a violation of Notary Code. These violations need to be enforced to ensure legal certainty for citizens. 2) The obstacle is the lack of awareness of the Notary to abide by a code of ethics, and supplies obtained Notary is not enough for his education, and still overlapping provisions of the code of conduct between the supervision of the Honorary Board and the Supervisory Council of Notaries. In an effort to prevent and reduce the occurrence of violations of the Code notary in Depok then the WCA Board and the Supervisory Council of Notaries to guidance, supervision, guidance and counseling. Included in providing strict sanctions as part of the coaching. Doing awards (reward) and punishment to the Notary in implementing the Notary Code provisions.Keywords: Judicial Review; Settlement; Breach; The Code; Notary.